INTEGRASI-INTERKONEKSI PERAN PERGURUAN TINGGI DALAM MENINGKATKAN KEMAMPUAN ENTREPRENEUR SKILL DAN MEMPERSIAPKAN COMPETITIVE ADVANTAGE DUNIA KERJA ERA DIGITAL SOCIETY 5.0 - Zathu Restie Utamie; Muhammad Iqbal Fasa (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN - SINTA 4, 2023)
Entrepreneurship education plays an important role in the development of entrepreneurial skills in individuals. It is time for universities based on teaching methods to switch to practicing methods, whose main focus is practical experience (practical work experience). This study used qualitative research methods. The results of this study found that UIN Raden Intan Lampung carried out various programs including: (1) Job Seeking Activities; (2) Entrepreneurship Training Activities; (3) Population Education Implementation Activities Through Compulsory General Lecture Materials (MKWU); (4) JOB FAIR activities; (5) Activities to prepare career center manuals; (6) OJK Teaching Activities to 1,000 students throughout Lampung Province; (7) Tracer Study Activities; (8) Pre-Employment Card Dissemination Assistance Activities; (9) Business Plan competition activities; (10) Webinar Activities "Tips and Trick How To Achieve LPDP and Mora Scholarships; (11) Astra Goes To Campus Workshop "Introduction to Insurance Business and Vehicle Financing"; (12) Assessment and Counseling Center Activities; (13) Higher Education Communication Forum Activities and the Ministry of Manpower; (14) Cooperation between the Tanggamus Regency Government and UIN Raden Intan Lampung regarding the Implementation of the CAT Test and the Fit Proper Test for the Election of Village Heads of Tanggamus Regency. The several steps that need to be taken by Raden Intan Lampung State Islamic University include: (1) Updating the entrepreneurship curriculum; (2) Digital Preneur Training and Workshops; (3) Collaboration with the Government, Banks and other stakeholders; (4) Field Competency Strengthening; (5) Building an Entrepreneurship Ecosystem